INTERPRETATION OF ETHNOPSYCHOLOGICAL DATA IN THE WORKS OF EASTERN SCHOLARS - Alimbayeva Shakhlo Tursunovna (Bright Mind Publishing, 2025)
This article analyzes the psychological expression of the people's psyche, national identity and cultural values in the works of oriental scholars. The author's work shows the harmony of folk customs, manners, human qualities and ethnopsychological thinking. The article examines ethnopsychological ideas in the works of oriental scholars from the perspective of modern psychology
Keywords: Oriental thinkers, ethnopsychology, people's psyche, national identity, manners, spirituality, values.